Increasing Vocabulary Mastery Through Kahoot: A Classroom Action Research at SMP Bhakti Pertiwi : Penelitian - Wildani Mukhollafah; Sofyan Adi Pranata; Mutiatul Ummah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aimed to increase students' vocabulary proficiency by utilizing Kahoot! as an interactive learning tool at SMP Bhakti Pertiwi. It addressed the core issue of inadequate English vocabulary mastery, which impeded students' effective communication skills. The research employed the Classroom Action Research (CAR) model by Kemmis and McTaggart, conducted across four phases: planning, action implementation, observation, and reflection. Participants included 26 eighth-grade students. Data collection involved vocabulary tests, classroom activity observations, and student feedback surveys. Results demonstrated a marked increase in average vocabulary scores, rising from 58.2 in the pre-cycle to 72.6 in Cycle I and further to 84.1 in Cycle II. Additionally, students' motivation and participation exhibited substantial enhancements. These outcomes indicated that Kahoot! integration effectively bolstered vocabulary acquisition and created a more dynamic and engaging English learning atmosphere. Consequently, the findings suggest that game-based educational platforms, such as Kahoot!, can be seamlessly incorporated into middle school English curricula to promote greater student involvement and enhance vocabulary retention.